Clinical Evaluation of Corridor Disease in Bos indicus (Boran) Cattle Naturally Infected With Buffalo-Derived Theileria parva - Cook, Elizabeth A. J.; Sitt, Tatjana; Poole, E. Jane; Ndambuki, Gideon; Mwaura, Stephen; Chepkwony, Maurine C.; Latre de Late, Perle; Miyunga, Antoinette A.; van Aardt, Richard; Prettejohn, Giles; Wragg, David; Prendergast, James G. D.; et al. (Frontiers in Veterinary Science, 2021)
Corridor disease (CD) is a fatal condition of cattle caused by buffalo-derived Theileria parva. Unlike the related condition, East Coast fever (ECF), which results from infection with cattle-derived T. parva, CD has not been extensively studied. We describe in detail the clinical and laboratory findings in cattle naturally infected with buffalo-derived T. parva. Forty-six cattle were exposed to buffalo-derived T. parva under field conditions at the Ol Pejeta Conservancy, Kenya, between 2013-2018. The first signs of disease observed in all animals were nasal discharge (mean day of onset 9 days post exposure), enlarged lymph nodes (10 days post exposure) and pyrexia (13.7 days post exposure). Coughing and laboured breathing were observed in over 50% of animals (14 days post exposure). Less commonly observed signs, corneal oedema (22%) and diarrhoea (11%), were observed later in the disease progression (19 days post exposure). All infections were considered clinically severe and forty-two animals succumbed to infection. The mean time to death across all studies was 18.4 days. The mean time from onset of clinical signs to death was 9 days and from pyrexia to death was 4.8 days indicating a relatively short duration of clinical illness. There were significant relationships between days to death and the days to first temperature (Chi2=4.00, p=0.046) and days to peak temperature (Chi2=25.81, p=0.001). These clinical indicators may be useful for assessing severity of disease in the future. All infections were confirmed by the presence of macroschizonts in lymph node biopsies (mean time to parasitosis was 11 days). Piroplasms were detected in the blood of two animals (4%) and 20 (43%) animals seroconverted. In this study we demonstrate the successful approach to an experimental field study for CD in cattle. We also describe the clinical progression of CD in naturally infected cattle including the onset and severity of clinical signs and pathology. Laboratory diagnoses based on examination of blood samples are unreliable and alternatives may not be available to cattle keepers. The rapid development of CD requires recognition of the clinical signs which may be useful for early diagnosis of the disease and effective intervention for affected animals.